Temperature sensing using sulfur-doped carbon nanoparticles. (July 2018) - Sadhanala, Hari Krishna; Senapati, Subrata; Nanda, Karuna Kar
Abstract: Temperature sensing at micro/nano scale with materials by direct fluorescence excitation is widely used in the recent years. Here, we report the green hydrothermal synthesis of sulfur-doped carbon nanoparticles (S-CNPs) from inexpensive precursors such as sucrose and sodium thiosulfate. The resultant S-CNPs exhibit luminescence both in aqueous and solid states. The variation of steady–state photoluminescence intensity of S-CNPs with temperature is investigated and the sensitivity of S-CNPs solid film with 355 nm excitation is found to be 2.63 × 10 −2 K −1, which is slightly higher than that with 532 nm excitation (2.15 × 10 −2 K −1 ). The activation energy is found to be 141.87 and 30.7 meV for 355 and 532 nm excitation, respectively. Similarly, the sensitivity of S-CNPs in solution is found to be 7.3 × 10 −3 K −1 and the the range of temperature is wider than physiological range (288–333 K) which suggests that S-CNPs can be used in the biological cells temperature sensing as well. Overall, the results suggest that S-CNPs can be used as nano thermometers. Graphical abstract: We report the effective synthesis of green luminescent sulfur doped carbon nanoparticles (S-CNPs) from sucrose and sodium thiosulfate using the hydrothermal method. On account of high chemical stability and bio-compatibility, we explored the S-CNPs for temperature sensing and yeast cell imaging. Image 1